Lipid metabolism contribute to the pathogenesis of IgA Vasculitis - Ying Liu; Min Wen; Qingnan He; Xiqiang Dang; Shipin Feng; Taohua Liu; Xuewei Ding; Xiaoyan Li; Xiaojie He (BMC, 2022)
Abstract Background and objectives The underlying mechanism of IgA vasculitis (IgAV) and IgA vasculitis with nephritis (IgAVN) remains unclear. Therefore, there are no accurate diagnostic methods. Lipid metabolism is related to many immune related diseases, so this study set out to explore the relationship of lipids and IgAV and IgAVN. Methods Fifty-eighth patients with IgAV and 28 healthy controls were recruited, which were divided into six separate pools to investigate the alterations of serum lipids according to the clinical characteristics: healthy controls group (HCs) and IgAV group (IgAVs), IgAVN group (IgAV-N) and IgAV without nephritis group (IgAV-C), initial IgAV group (IgAV0) and IgAV in treatment with glucocorticoids group (IgAV1). Results 31 identified lipid ions significantly changed in IgAVs with p < 0.05, variable importance of the projection (VIP) > 1 and fold change (FC) > 1.5. All these 31 lipid ions belong to 6 classes: triacylglycerols (TG), phosphatidylethanolamine (PE), phosphatidylcholine (PC), phosphatidylserine, ceramide, and lysophosphatidylcholine. TG (16:0/18:1/22:6) +NH4 over 888875609.05, PC (32:1) +H over 905307459.90 and PE (21:4)-H less than 32236196.59 increased the risk of IgAV significantly (OR>1). PC (38:6) +H was significantly decreased (p < 0.05, VIP>1 and FC>1.5) in IgAVN. PC (38:6) less than 4469726623 conferred greater risks of IgAV (OR=45.833, 95%CI: 6.689~341.070). Conclusion We suggest that lipid metabolism may affect the pathogenesis of IgAV via cardiovascular disease, insulin resistance, cell apoptosis, and inflammation. The increase of TG(16:0/18:1/22:6) + NH4, and PC(32:1) + H as well as PE (21:4)-H allow a good prediction of IgAV. PE-to-PC conversion may participate in the damage of kidney in IgAV. PC (38:6) + H may be a potential biomarker for IgAVN.